THE IMPLEMENTATION OF LEARNING VOCABULARY USING FLASHCARD FOR YOUNG CHILDREN THROUGH GOOGLE CLASSROOM - Yuliantari, I Gusti Ayu Winda; Padmadewi, Ni Nyoman; Budasi, I Gede (Jurnal Pendidikan Bahasa Inggris undiksha, 2021)
Vocabulary learning is one of the essential elements for young learners. This study aims to analyze the planning and implementation of flashcards in Google Classroom to teach vocabulary and analyze the advantages and disadvantages of flashcards in Google Classroom. This research is a case study with an English teacher in the fifth grade of elementary school. Data was collected using a list of observations and interview guides. The procedure for collecting data is conducting online observations in Google Classroom and conducting interviews with research subjects. The data collected was analyzed qualitatively with the analytical technique of Miles and Huberman. The results showed that there were four planning activities: checking the syllabus, determining the text or material to be taught, determining the teaching method, and preparing a lesson plan. Second, teachers do three stages in implementing flashcards in Google Classroom, namely Initial Activities, Core Activities, and Closing Activities. Third, the advantages of using flashcards in Google Classroom are motivating students to learn, avoiding boredom, building student interest, and helping students remember vocabulary according to pictures. This research implies that the use of flashcards to teach vocabulary using Google Classroom can positively impact students, especially young learners.